2018
DOI: 10.1108/par-01-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing performance by disclosing more: some evidence from Japanese companies

Abstract: Purpose The purpose of this study is to investigate the value relevance of corporate social responsibility disclosures (CSRDs) in English language annual reports in Japanese companies. Based on the stakeholder theory framework, the long-term effects of CSRD on financial and market performance are examined. There is relatively little research dealing with actual CSR reporting in Japanese companies. Design/methodology/approach Using modified versions of those given by Ohlson (1995) and Ruf et al. (2001), six d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Li et al (2016) find a positive association between CSR disclosure and firm value. Additionally, De Klerk et al (2015) and Kumarasinghe et al (2018) find that higher levels of CSR disclosure are positively associated with stock market performance. Although CSR reporting, CSR performance and its impact on a firm's value have been studied extensively, an area that has not been fully explored is its relationship with executive compensation.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2016) find a positive association between CSR disclosure and firm value. Additionally, De Klerk et al (2015) and Kumarasinghe et al (2018) find that higher levels of CSR disclosure are positively associated with stock market performance. Although CSR reporting, CSR performance and its impact on a firm's value have been studied extensively, an area that has not been fully explored is its relationship with executive compensation.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies in developed countries had observed companies' trend of using SR to enhance company reputation. For example, Kumarasinghe et al (2017) found that SR activities boost the nancial and market e ciency of Japanese companies, building on the legitimacy theory's hypothesis that companies would require more group disclosures following product changes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research that discusses the relevance value of CSR disclosure has been carried out worldwide with mixed results and resulting discussions. Based on research conducted by (Kumarasinghe et al, 2018;Nuriyanto et al, 2020;Saragih, 2020), disclosures made by companies, especially regarding CSR or social responsibility, are related to market responses to companies positively which indicates that CSR information provided disclosed a substantial relevance value. Many investors are already aware of the importance of the company's concern for social conditions and the surrounding environment.…”
Section: Value Relevance and Corporate Social Responsibility Disclosu...mentioning
confidence: 99%